Integration or Predictability? A Further Specification of the Functional Role of Gamma Oscillations in Language Comprehension - Wang, Lin; Zhu, Zude; Bastiaansen, Marcel (Frontiers in Psychology, 2012)
Abstract Gamma-band neuronal synchronization during sentence-level language comprehension has previously been linked with semantic unification. Here we attempt to further narrow down the functional significance of gamma during language comprehension, by distinguishing between two aspects of semantic unification: successful integration of word meaning into the sentence context, and prediction of upcoming words. We computed Event-Related Potentials (ERPs) and frequency band-specific Electroencephalogram (EEG) power changes while participants read sentences that contained a critical word that was (1) both semantically congruent and predictable (High-Cloze, HC), (2) semantically congruent but unpredictable (Low-Cloze, LC), or (3) semantically incongruent (and therefore also unpredictable; Semantic Violation, SV). The ERP analysis showed the expected parametric N400 modulation (HC < LC < SV). The time-frequency analysis showed qualitatively different results. In the gamma frequency range, we observed a power increase in response to the critical word in the HC condition, but not in the LC and the SV conditions. Additionally, in the theta frequency range we observed a power increase in the SV condition only. Our data provide evidence that gamma power increases are related to the predictability of an upcoming word based on the preceding sentence context, rather than to the integration of the incoming word's semantics into the preceding context. Further, our theta-band data are compatible with the notion that theta-band synchronization in sentence comprehension might be related to the detection of an error in the language input.